The influence of services marketing mix on the decision to choose a new living credit union in the city of Tebing Tinggi - Purba, Juliansen; Tinambunan, Yusnita; Pasaribu, Romindo M.; Malau, Anne Rumondang; Naibaho, Krismanto E.T (Junal Ilmu Manajemen, 2024)
The purpose of this research is to determine the influence of the service marketing mix on the decision to choose the New Life credit union in the city of Tebing Tinggi. The sampling technique was carried out using non-probability sampling with purposive sampling technique. The sample for this research was taken from 100 respondents and used quantitative data analysis techniques. Partial test results (t-test) were obtained from the results of the assessment of product variables and physical evidence which had a positive but not significant effect on the decision to choose a New Life credit union, price and location variables had a negative and not significant effect on the decision to choose a New Life credit union, promotion variables, people, and processes have a positive and significant influence. The results of the F test for the variables product, price, promotion, location, people, process, and physical evidence simultaneously have a positive and significant influence on the decision to choose the New Life credit union. And the results of the coefficient of determination test (R2) for product, price, promotion, location, people, process and physical evidence variables can explain the decision to choose the New Life credit union in Tebing Tinggi city of 0.492 or 49.2%, the remaining 50.8% is explained by other variables not examined in this research.